Revisiting Post-ICU Admission Fluid Balance Across Pediatric Sepsis Mortality Risk Strata: A Secondary Analysis of a Prospective Observational Cohort Study - Mihir R. Atreya, MD, MPH; Natalie Z. Cvijanovich, MD; Julie C. Fitzgerald, MD, PhD; Scott L. Weiss, MD, MSCE; Michael T. Bigham, MD; Parag N. Jain, MD; Kamal Abulebda, MD; Riad Lutfi, MD; Jeffrey Nowak, MD; Neal J. Thomas, MD, MSc; Torrey Baines, MD; Michael Quasney, MD, PhD; et al. (Critical Care Explorations, 2024)
OBJECTIVES:. Post-ICU admission cumulative positive fluid balance (PFB) is associated with increased mortality among critically ill patients. We sought to test whether this risk varied across biomarker-based risk strata upon adjusting for illness severity, presence of severe acute kidney injury (acute kidney injury), and use of continuous renal replacement therapy (CRRT) in pediatric septic shock. DESIGN:. Ongoing multicenter prospective observational cohort. SETTING:. Thirteen PICUs in the United States (2003–2023). PATIENTS:. Six hundred and eighty-one children with septic shock. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. Cumulative percent PFB between days 1 and 7 (days 1–7 %PFB) was determined. Primary outcome of interest was complicated course defined as death or persistence of greater than or equal to two organ dysfunctions by day 7. Pediatric Sepsis Biomarker Risk Model (PERSEVERE)-II biomarkers were used to assign mortality probability and categorize patients into high mortality (n = 91), intermediate mortality (n = 134), and low mortality (n = 456) risk strata. Cox proportional hazard regression models with adjustment for PERSEVERE-II mortality probability, presence of sepsis-associated acute kidney injury on day 3, and use of CRRT, demonstrated that time-dependent variable days 1–7%PFB was independently associated with an increased hazard of complicated course. Risk-stratified analyses revealed that each 10% increase in days 1–7 %PFB was associated with increased hazard of complicated course only among patients with high mortality risk strata (adjusted hazard ratio 1.24 (95% CI, 1.08–1.43), p = 0.003). However, this association was not causally mediated by PERSEVERE-II biomarkers. CONCLUSIONS:. Our data demonstrate the influence of cumulative %PFB on the risk of complicated course in pediatric septic shock. Contrary to our previous report, this risk was largely driven by patients categorized as having a high mortality risk based on PERSEVERE-II biomarkers. Incorporation of such prognostic enrichment tools in randomized trials of restrictive fluid management or early initiation of de-escalation strategies may inform targeted application of such interventions among at-risk patients.